Exploring the Association Between ABO Blood Groups and Blood Glucose Levels in Known Cases of Type 2 Diabetes Mellitus - Makhija, Mahima; Jain, Shreyansh; Jain, Smita; Kumar, Susheel; Bansal, Alka (Scripta Medica, 2025)
Background/Aim: ABO blood types have long been linked to diverse predispositions to a number of diseases, including diabetes mellitus. Blood group B and type 2 diabetes are significantly positively correlated, while blood group O and DM have a negative correlation, according to several studies. This study focused a step further to evaluate whether blood type affects HbA1c, postprandial blood glucose (PPBG) and fasting blood glucose (FBG) levels in individuals with type 2 diabetes.Methods: A cross-sectional study was conducted on 90 patients with type 2 diabetes, aged 18 to 75 years, from the medicine department of RUHS Hospital in Jaipur, in May 2023. Detailed information regarding a number of important study variables, such as blood groups, HbA1c levels, PPBG and FBG, were gathered through extensive laboratory tests. The gathered information was carefully examined utilising statistical methods in order to derive conclusions.Results: Chi-square test revealed that blood groups and all blood sugar level variables in type 2 diabetic patients are independent attributes (p > 0.05) and no association exists between them.Conclusion: The study concludes that type 2 diabetes, once developed, blood groups do not affect the severity and status of the disease, although they may have an initial contribution to susceptibility.